Impact Assessment of Land Use/ Land Cover Change on Soil Erosion and Rural Livelihood in Andit Tid Watershed, North Shewa, Ethiopia - , Abrham Tezera, Tilashwork Chanie, Tesfaye Feyisa, Abdlesemed Jemal (Archives of Current Research International, 2015)
Land use, which is use of land by human for different purposes, is influenced by two broad sets of forces human needs (socio-economic) and environmental features and processes (biophysical). The study was carried out at Andit Tid watershed one of SCRP research unit founded in 1982, located on 39° 43’E 9°48’N. This research has aimed to assess the trend and main driving force of land use and land cover change (LULCC) within the catchment / watershed during the last two decades and its impact on soil erosion. Structural questioner was used to collect social data from 8% of the total household. Landsat 5 and Landsat 8 Enhanced Thematic Mapper (ETM) and supervised image classification used to identify land use/ land cover change of the study area for 1994 and 2014 years, respectively. TESTMAIN and SPSS version 16 Statistical software’s were used for Soil loss calculation and social data analysis, respectively. The result indicates that, there is expansion of cultivated land by 11.33% (44.55ha) while reduction in natural shrub lands by 7.3% (35.73ha). The main driving forces of land use land cover change are high number of family member, small land holding size and minimum asset own per household, lower educational level of the household, the household mainly occupied on agriculture and there is lack of animal feed. This change forced farmers to collect cereal crops based on suitability area, sale livestock, use organic and inorganic fertilizer and use improved variety due to low crop productivity. The LULC change has an impact on decline soil fertility, cause serious soil erosion problem with in farmland/watershed. The result also indicated that soil loss reached 3655 ton per annum from the watershed. Therefore, proper handling and land use system need to be implemented, rainwater harvesting structures and soil and water conservation practice need to be encouraged in order reduce soil loss.